Assistance with Literacy and Numeracy Activities in the Teaching Campus 4 Program - Estu Handayani; Yeni Hilma Dwiyanti (Trescode Green Organization, 2023)
The COVID-19 pandemic that hit Indonesia had an impact on teaching and learning activities which resulted in the uptake of students' understanding at school on matters related to literacy and numeracy to decrease and not be optimal. This is because learning during a pandemic is carried out online or online. Conditions post-pandemic COVID-19 need to be rearranged, one of which is with the Teaching Campus activities. SMP Sunan Giri I Banyuwangi is one of the schools selected for the Campus Teaching Literacy and Numeracy program. Teaching campus activities help improve the literacy and numeracy skills of students at SMP Sunan Giri I where it was found that some students do not understand simple calculations and there are still many students with very low literacy awareness. The results of the implementation of the Merdeka Campus community service at SMP Sunan Giri I Grogol can be seen from the enthusiasm of the students in receiving learning about literacy and numeracy creatively and interestingly and making students feel comfortable in participating in a series of activities.